Validation of the GeneXpert Xpress SARS-CoV-2 PCR assay using saliva as biological specimen - Sara Nunes Vaz; Daniele Souza de Santana; Eduardo Martins Netto; Wei-Kung Wang; Carlos Brites (Brazilian Journal of Infectious Diseases, 2021)
In the pandemic, rapid and accurate detection of SARS-CoV-2 is crucial in controlling the outbreak. Recent studies have shown a high detection rate using saliva/oral fluids as specimens for laboratory detection of the virus. We intended to evaluate the test performance of the Xpert Xpress SARS-CoV-2 cartridge assay in comparison to a conventional qRT-PCR testing, using saliva as biological specimen. Forty saliva samples from symptomatic participants were collected. Conventional qRT-PCR was performed for amplification of E and RdRp genes and the Xpert Xpress SARS-CoV-2 assay amplified E and N2 genes. In the conventional assay, the median cycle threshold value of the E gene was 34.9, and of the RdRp gene was 38.3. In the Xpert Xpress assay, the median cycle threshold value of the E gene was 29.7, and of the N2 gene was 31.6. These results can allow a broaden use of molecular tests for management of COVID-19 pandemic, especially in resources-limited settings.